Pengembangan Literasi dan Numerasi di SD Negeri 060840, Medan Barat, Kota Medan - Joy Nicholas Matthew Sigalingging; Faiz Albar Nasution (Yayasan Literasi Sains Indonesia, 2023)
This text discusses a final project undertaken by an author as part of their requirements for Field Work Practice 1 and Independent Campus Learning and Teaching Activity (ICLTA) at State Elementary School 060840 in Medan City. The author observed and identified issues faced by students, such as a lack of interest in learning and limitations in literacy and numeracy skills. To address this, the author developed a mini project aiming to improve students' learning interest, literacy, and numeracy skills at SDN 060840 Medan. They worked with students from grades one to six, utilizing social group work stages and Focus Group Discussion (FGD) as the research method. The project resulted in a significant enhancement of students' literacy and numeracy skills, leading to improved academic performance and practical application of knowledge. Additionally, the project lays the groundwork for continuous learning in the future.